Hydration of MgO/SiO2 and Portland cement mixtures: A structural investigation of the hydrated phases by means of X-ray diffraction and solid state NMR spectroscopy. (December 2017) - Martini, Francesca; Tonelli, Monica; Geppi, Marco; Ridi, Francesca; Borsacchi, Silvia; Calucci, Lucia
Abstract: The phases formed during the hydration of several MgO/SiO2 and Portland cement mixtures were investigated by performing X-ray diffraction and 29 Si and 27 Al solid state NMR experiments on samples hydrated for 1, 7 and 28 days. The structural properties and relative amount of magnesium silicate hydrate (M-S-H) and calcium silicate hydrate (C-S-H) gels, which form as separate phases, were found to significantly depend on the initial composition of the mixtures. Faster hydration kinetics was observed for all mixtures with respect to the "pure" MgO/SiO2 and Portland cement samples, pH and excess of silica playing a major role. Moreover, the addition of the MgO/SiO2 mixture to Portland cement affects the formation of aluminum-containing hydrated phases.